Evaluation of effects of nitrogen and magnesium fertilization on rice yield and fertilizer nitrogen efficiency using 15N tracer technique - Choudhury, T. M. A.; Khanif, Y. M. (Taylor and Francis Group, 2001)
Rice crop suffers from magnesium (Mg) deficiency in many locations of Muda Irrigation Scheme, Kedah, Malaysia. As a result nitrogen (N) efficiency is low in rice culture. It is necessary to evaluate the effects of Mg fertilization on rice yield and N use efficiency. A greenhouse experiment was conducted at Universiti Putra Malaysia during May to September 1998 to evaluate the effects of N and Mg fertilization on rice yield and fertilizer N efficiency in two soils (Guar and Hutan series). Nitrogen was applied as 15N labeled urea. Nitrogen and Mg application increased grain yield significantly in both the soils. Regression analysis indicated that estimated grain yield response to added N was linear in Guar series while it was quadratic in Hutan series. Estimated grain yield response to added Mg was quadratic in nature in both the soils. 15N atom excess in both grain and straw increased significantly with increasing N rates. Magnesium fertilization increased fertilizer N uptake and recovery (%) of fertilizer N significantly. These findings suggest that there is a prospect to increase rice yield and fertilizer N efficiency through Mg fertilization.